Golf skills, training, techniques - Stables, Matt (The Crowood Press, 2013)
Crowood Sports Guides provide sound, practical advice that will make you into a better sportsperson, whether you are learning the basic skills, discovering more advanced techniques or reviewing the fundamentals of your sport. Golf is the latest addition to this popular sports guide series and covers choosing the right clubs and clothing, improving your swing to hit longer and straighter shots consistently and also improving your putting, short game and bunker play